Concordance of hypervascular liver nodule characterization between the organ procurement and transplant network and liver imaging reporting and data system classifications. Issue 2 (5th November 2014) - Bashir, Mustafa R.; Huang, Rong; Mayes, Nicholas; Marin, Daniele; Berg, Carl L.; Nelson, Rendon C.; Jaffe, Tracy A.
<x xml:space="preserve">Abstract</x> Purpose To determine the rate of agreement between the Organ Procurement and Transplant Network (OPTN) and Liver Imaging Reporting and Data System (LI‐RADS) classifications for hypervascular liver nodules at least 1 cm in diameter, and for patient eligibility for hepatocellular/MELD (Model for Endstage Liver Disease) exception points. Materials and Methods This retrospective study was approved by our Institutional Review Board and was compliant with the Health Insurance Portability and Accountability Act. The requirement for informed consent was waived. This study included 200 hypervascular hepatocellular nodules at least 1 cm in diameter on computed tomography (CT) or magnetic resonance imaging (MRI) examinations in 105 patients with chronic liver disease. Three radiologists blinded to clinical data independently evaluated nodule characteristics, including washout, capsule, size, and size on prior examination. Based on those characteristics, nodules were automatically classified as definite hepatocellular carcinoma (HCC) or not definite HCC using both the OPTN and LI‐RADS classifications. Using these classifications and the Milan criteria, each examination was determined to be "below transplant criteria, " "within transplant criteria, " or "beyond transplant criteria." Agreement was assessed between readers and classification systems, using Fleiss' kappa, intraclass correlation coefficients (ICCs), and simple proportions. Results Interreader agreement was moderate for nodule features (κ = 0.59–0.69) and nodule classification (0.66–0.69). The two systems were in nearly complete agreement on nodule category assignment (98.7% [592/600]) and patient eligibility for transplant exemption priority (99.4% [313/315]). A few discrepancies occurred for the nodule feature of growth (1.3% [8/600]) and for nodule category assignment (1.3% [8/600]). Conclusion Agreement between the OPTN and LI‐RADS classifications is very strong for categorization of hypervascular liver nodules at least 1 cm in diameter, and for patient eligibility for hepatocellular/MELD exception points. Interreader variability is much higher than intersystem variability. J. Magn. Reson. Imaging 2015;42:305–314.